Indian library chronology - Kumar, P S G (Ahmedabad Allied, 2000)
Indian Library Chronology was first published in 1977.It comprehended about 4,600 enteries from 3000 B.C. to 1975 A.D. This book is the revised and updated edition covering till 1998. It is divided into two parts:Before Independence( till 1947)and After I
Keywords: Libraries-India-History-3000 BC-1947; Libraries-India-History-1948-1998; Libraries-India-History-Chronology